The Role of Strategic Orientation, Government Regulation on Green Supply Chain Management to Improve Business Performance - Hadiahti Utami; Nanang Adie Setyawan; Irin Mirrah Luthfia; Sri Eka Sadriatwati; Andi Setiawan; Suwardi, Suwardi; Saptianing, Saptianing (International Journal of Education, Vocational and Social Science, 2024)
The increasing challenges of economic competition and issues related to environmental maintenance require business actors to consider the actions that will be taken in order to survive and exist in the recovery after the co-19 pandemic while still paying attention to the surrounding environmental conditions, the application of Green Supply Chain Management (GSCM) is a topic that is being echoed in the industrial world today. The population of this study were Semarang Batik MSME players. While the sampling technique used in this research is purposive sampling method. The number of research samples was 100 samples. The research technique used is linear regression analysis and Moderation Regression Analysis using SPSS version 25. The output model in this study is expected to make a positive contribution to MSME actors in an effort to realize their business continuity, both in the form of managerial implication suggestions and the formulation of scientific articles and measurement instruments. Managerial advice is aimed at the local government in formulating program policies to maintain the existence of Semarang batik entrepreneurs who are currently being affected by issues related to environmental friendliness.